Efektivitas Penggunaan Google Form Dalam Pengelolaan Nilai Asesmen Sumatif Asesmen Sumatif Akhir Semester - Nadhirah (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the effectiveness of using Google Forms in managing the final semester summative assessment scores for the 2025/2026 academic year at MTsN 1 Maluku Tengah as an effort to improve the efficiency of assessment administration. The research employed a quantitative approach with a survey design, involving 34 teachers as respondents selected because they were directly engaged in the processes of data entry, score processing, and reporting. The research instrument consisted of a closed-ended questionnaire using a Likert scale measuring aspects such as time efficiency, minimization of input errors, accessibility and data management, score transparency, ease of report generation, and institutional technical support. The findings indicate that the majority of teachers expressed positive responses toward the use of Google Forms. A total of 94.10% reported that Google Forms reduced score processing time through automated correction features, while 91.10% stated that the application minimized data input errors. Additionally, 94.20% noted that Google Forms enhanced assessment transparency by providing quick and accurate feedback. However, 20.6% of teachers still experienced challenges related to digital literacy when operating the application. Overall, this study demonstrates that Google Forms is an effective, efficient, and adaptive tool for supporting score management in madrasahs and contributes to improving the quality of assessment administration in the digital era.